Pharmacological Strategies to Contend Against Myocardial Reperfusion Damage: Diverse Chemicals for Multiple Targets - Correa, F.; Martinez-Abundis, E.; Hernandez-Resendiz, S.; Garcia, N.; Buelna-Chontal, M.; Arreguin, F.; Zazueta, C. (Current Medicinal Chemistry, 2010)
Acute myocardial infarction is a frequent and disabling disease. Paradoxically, reperfusion, the most effective treatment to reduce infarct size, can both protect and kill. Although reperfusion protects by preventing lesions occurring during prolonged ischemia, it causes damage because reflow is associated with an unbalance between oxygen availability and metabolic demand, altered ionic homeostasis, and reactive oxygen species (ROS) generation. Recently, more players in myocardial reperfusion injury have been described: protein kinase C (PKC) and members of the MAP kinase, which activate downstream cascades that may activate intricate processes compromising cardiac recovery after ischemia. All together, such mechanisms promote endothelial and vascular dysfunction, sequels of impaired blood flow, metabolic and contractile dysfunction, dysrhythmia, cellular necrosis and apoptosis. Different pharmacological agents, as well as mechanical strategies, have been used to challenge the outcome of the complex interactions among these mechanisms and with others. In this review, we focused on the potential of different compounds used in animal models and in the clinical practice to improve the prognosis after post-ischemic reperfusion. We also review mechanisms activated during reperfusion injury and the structure-activity relationship between some of the cardioprotective chemicals and their cellular targets.
Keywords: cardioprotection